2013
DOI: 10.4103/1119-3077.113460
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy of Prader orchidometer in measuring testicular volume

Abstract: The result of this study has shown that measuring the testicular volume by Prader orchidometer overestimates the actual testicular volume.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 25 publications
1
12
0
Order By: Relevance
“…Moreover, they constrain the observer to specific size choices ranging from 1 cc to 25 cc, and the effect of pairing a testicle with a particular size (such as picking 10 cc vs 8 cc) can lead to an error of up to 20%. To this end, Mabieri et al, when comparing orchidometer values with volumes of dissected testicles, showed that an orchidometer consistently overestimates testicular volume by 25%, but there still remains significant correlation between the two measurements [12]. In theory, any error in the orchidometric measurements should distribute itself across both testicles and only influence the absolute volume, not the volume difference.…”
Section: Page 11mentioning
confidence: 95%
“…Moreover, they constrain the observer to specific size choices ranging from 1 cc to 25 cc, and the effect of pairing a testicle with a particular size (such as picking 10 cc vs 8 cc) can lead to an error of up to 20%. To this end, Mabieri et al, when comparing orchidometer values with volumes of dissected testicles, showed that an orchidometer consistently overestimates testicular volume by 25%, but there still remains significant correlation between the two measurements [12]. In theory, any error in the orchidometric measurements should distribute itself across both testicles and only influence the absolute volume, not the volume difference.…”
Section: Page 11mentioning
confidence: 95%
“…[2,13] Since the US was used in measuring the testicular volume, several equations were used to calculate the volume, one of the most common equation was formulated by Lambert 1951 (0.71 * length * width * height). [2,6,14] Regarding the fact the cut-off point didn't determine ,previous studies showed various results in measuring testicular volume relying on the using method. [2,15] The results of the current studies showed that the mean scores of testicles volume were 12.0±5.0 for right testicular and 11.2±4.7 for left testicular, which consistent with other studies, in India studies the mean scores for right and left testicles were 11.83±3.2 and 11.08±2.8 respectively, [11] and in Albania study the mean scores were 12.8 and 12.4 for right and left testicles respectively .…”
Section: Result:-mentioning
confidence: 99%
“…MRI brain focussing on the pituitary–hypothalamic region and olfactory placodes was performed at baseline for patients in groups A and B using a 3T scanner and was reported by a dedicated radiologist. Testicular volume was assessed by Praders' orchidometer and by ultrasound …”
Section: Methodsmentioning
confidence: 99%